Attitude towards the Vocational Training Programmes of Krishi Vigyan Kendra, Kollam, Kerala - M, Geethu A; Bindu, Podikunju (Journal of Extension Education, 2020)
Krishi Vigyan Kendras (KVK) are one of the most vital establishment pledged for the dissemination of farm technology in the grass root level. The present study was conducted at Krishi Vigyan Kendra, Kollam, Kerala with 75 respondents, 15 each from five major vocational trainings organized at the KVK during the last five years. The trainees were personally interviewed with a well-structured and pre tested interview schedule. The present study on attitude of respondents revealed that more than half of the total beneficiaries have higher positive attitude towards the KVK.